Sensory evaluation: the last hurdle in varietal development of yams (Dioscorea rotundata, poir) in Ghana - Otoo, E.; Asiedu, Robert (2009)
In variety development, sensory evaluation is not only the most important hurdle after all the necessary agronomic characteristics have been developed but also a major determinant of acceptability of the variety, as well as a major determinant in the subsequent adoption and use of the variety. Eight yam genotypes out of thirty-six genotypes evaluated for yield, pest and disease tolerance and stability over a three year period, plus 3 farmers’ checks were assessed on parameters such as enzymatic oxidation, colour attractiveness, aroma, taste, texture and overall acceptability in relation to farmers’ checks (Dente, Brass and Dorban). Gender differences existed in the degree of perception of texture and taste of yams. KUP__2000/001 was the overall best genotype with respect to general acceptability in all agroecologies followed by TDr_89/02665, 2000/001, TDr__ 89/02660, TDr__95/19177, Dente, Brass, Dorban, TDr__95/01932, TDr__95/01544 and TDr__98/02877 in that order. The results of this study indicated that accessions KUP_2000/001, TDr_89/02665 and 2000/001 were the most preferred accessions with respect to sensory evaluation. After clearing this all important hurdle of sensory evaluation, genotypes KUP_2000/001, TDr_89/02665 and 2000/001 were release as varieties CRIPona, MankrongPona and CRIKukrupa respectively in 2005.